MENINGKATKAN HASIL BELAJAR MATEMATIKA OPERASI HITUNG SATUAN WAKTU MENGGUNAKAN MEDIA PEMBELAJARAN SMART WATCH DI SD - Moh. Agus Syairofi Syafi’; Rina Kurniawati (Universitas Islam Raden Rahmat Malang, 2023)
This study was prepared with the aim of improving the learning outcomes of mathematics in the material of counting units of time using smart watch learning media for class IIIA students of Ma'arif YPM Wonocolo Elementary School, Taman Sidoarjo in the 2022/2023 academic year. The learning outcomes referred to in this study are increasing the value of math lessons on the material of calculating the unit of time. This type of research is classroom action research (PTK), where the researcher is the learning teacher while the students are the learning subjects. this research was conducted in the even semester of the 2022/2023 school year, namely in February to March. The subjects of this study were students of class IIIA Ma'arif YPM Wonocolo Elementary School, Taman Sidoarjo in the 2022/2023 academic year consisting of 26 students. The object of research is the learning outcomes of students in mathematics subjects. Data collection techniques using observation and interviews. The data were analyzed descriptively and presented using tables and graphs. The results showed an increase in student learning outcomes, namely in cycle I of 65%, then in cycle II it increased to 80%. This means that there was an increase of 15%. thus the use of smart watch learning media in math lessons can improve the learning outcomes of class IIIA students of Ma'arif YPM Wonocolo Elementary School, Taman Sidoarjo in the 2022/2023 academic year.